Plasticity of Subventricular Zone Neuroprogenitors in MPTP (1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine) Mouse Model of Parkinson's Disease Involves Cross Talk between Inflammatory and Wnt/β-Catenin Signaling Pathways: Functional Consequences for Neuroprotection and Repair - L'Episcopo, Francesca (Society for Neuroscience, 2012)
In Parkinson's disease (PD), neurogenesis is impaired in the subventricular zone (SVZ) of postmortem human PD brains, in primate nonhuman and rodent models of PD. The vital role of Wingless-type MMTV integration site (Wnt)/β-catenin signaling in the modulation of neurogenesis, neuroprotection, and synaptic plasticity coupled to our recent findings uncovering an active role for inflammation and Wnt/β-catenin signaling in MPTP-induced loss and repair of nigrostriatal dopaminergic (DAergic) neurons prompted us to study the impact of neuroinflammation and the Wnt/β-catenin pathway in the response of SVZ neuroprogenitors (NPCs) in MPTP-treated mice. In vivo experiments, using bromodeoxyuridine and cell-specific markers, and ex vivo time course analyses documented an inverse correlation between the reduced proliferation of NPCs and the generation of new neuroblasts with the phase of maximal exacerbation of microglia reaction, whereas a shift in the microglia proinflammatory phenotype correlated with a progressive NPC recovery. Ex vivo and in vitro experiments using microglia–NPC coculture paradigms pointed to NADPH-oxidase (gpPHOX(91)), a major source of microglial ROS, and reactive nitrogen species as candidate inhibitors of NPC neurogenic potential via the activation of glycogen synthase 3 (pGSK-3β(Tyr216)), leading to loss of β-catenin, a chief downstream transcriptional effector. Accordingly, MPTP/MPP(+) (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) caused β-catenin downregulation and pGSK-3β(Tyr216) overexpression, whereas manipulation of Wnt/β-catenin signaling with RNA interference-mediated GSK-3β knockdown or GSK-3β antagonism reversed MPTP-induced neurogenic impairment ex vivo/in vitro or in vivo. Reciprocally, pharmacological modulation of inflammation prevented β-catenin downregulation and restored neurogenesis, suggesting the possibility to modulate this endogenous system with potential consequences for DAergic neuroprotection and self-repair.